2019
DOI: 10.1007/s10902-019-00124-8
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Effects of Social Support in the Association Between Problems in Childhood and Adolescence and Well-Being in Adult Domestic Adoptees

Abstract: Research concerning adulthood and adoption has gained popularity in recent years, but there are very few studies involving positive variables of adjustment. Adopted people are believed to have more behavioral and emotional problems in childhood than the general population. Previous research suggests overall continuity of functioning in later life. However, certain variables might change that continuity. Through Structural Equation Modeling analyses, this paper assesses the mediating role of social support in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Many prior studies have shown the importance of social support in promoting well-being (Sanchez-Sandoval et al, 2019;Cobo-Rend on et al, 2020;Xie et al, 2020), as an example, for medical students, the role of social support in promoting a greater sense of well-being was evident (Biro et al, 2010). This is compatible with our research results.…”
Section: Discussionmentioning
confidence: 99%
“…Many prior studies have shown the importance of social support in promoting well-being (Sanchez-Sandoval et al, 2019;Cobo-Rend on et al, 2020;Xie et al, 2020), as an example, for medical students, the role of social support in promoting a greater sense of well-being was evident (Biro et al, 2010). This is compatible with our research results.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the importance of the social context features (Lerner, 2006). Specifically, family is universally seen as providing a critical environment that, when nurturing and protective, can trigger relevant improvements and stimulate a remarkable capacity for recovery from early adversities and abandonment (which may represent the most traumatic event in an adoptive child's life) (e.g., Canzi, Rosnati, & Miller, 2018, Canzi, Rosnati, Palacios, & Roman, 2018; Palacios & Brodzinsky, 2010; Paniagua et al, 2018; Rosnati & Marta, 1997; Sánchez‐Sandoval et al, 2020; Walkner & Rueter, 2014; Whitten & Weaver, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, they encompass a number of educational, material and support services to help adoptive families with difficulties related to the adoption situation (Teska, 2018). These measures meet the idea of Pedro-Viejo (2017) and of Sánchez-Sandoval et al (2019) on the importance of a post-adoption work capable of promoting the necessary resources so families can face the adaptation challenges imposed by the condition of adoption, both in the initial adaptation and throughout the family life cycle. It should be noted that the literature on the initial adaptation time in adoptive families is scarce, and it is common to take the first years of family life, that is, the postpartum period of a biological parenthood, as reference for the study of this phenomenon (Kay et al, 2014).…”
Section: Introductionmentioning
confidence: 85%